Membangun Kesadaran Lingkungan Pada Remaja Di Asrama St. Angela Sedayu - Fridayani, Januari Ayu; Istono, Minta; Puri, Anindita Dewangga (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
The community service program aimed at raising environmental awareness among the youth at St. Angela Sedayu Girls' Dormitory was conducted through three main phases: initial observation, outreach, and evaluation. The outreach provided education on environmental management, energy conservation, as well as the concepts of sustainable food consumption and slow fashion. This approach was supported by the moral and spiritual values from the encyclical Laudato Si', which emphasizes the importance of caring for the earth as our "common home."The results of the outreach demonstrated an increase in understanding and behavioral changes among the youth regarding waste sorting, reduced plastic consumption, and energy conservation. Additionally, the youth began adopting sustainable food consumption practices and decreasing their reliance on fast fashion. Although the program did not include long-term monitoring, the observed behavioral changes indicate potential sustainability if supported by appropriate management strategies. As a recommendation, the dormitory could implement a more effective waste sorting system, promote energy conservation, encourage local food consumption, and support slow fashion through creative programs. With a sustainable approach, the dormitory is expected to continue fostering an environmentally friendly culture among the youth.